Wall Shear Stress Predicts Media Degeneration and Biomechanical Changes in Thoracic Aorta - Kiema, Miika; Sarin, Jaakko K.; Kauhanen, S. Petteri; Torniainen, Jari; Matikka, Hanna; Luoto, Emma-Sofia; Jaakkola, Pekka; Saari, Petri; Liimatainen, Timo; Vanninen, Ritva; Ylä-Herttuala, Seppo; Hedman, Marja; et al. (Frontiers in Physiology, 2022)
Objectives. In thoracic aortic aneurysm (TAA) of the ascending aorta (AA), AA is progressively dilating due to the weakening of the aortic wall. Predicting and preventing aortic dissections and ruptures in TAA continues to be challenging, and more accurate assessment of the AA dilatation, identification of high-risk patients, and timing of repair surgery are required. We investigated whether wall shear stress (WSS) predicts pathological and biomechanical changes in the aortic wall in TAA. Methods. The study included 12 patients with bicuspid (BAV) and 20 patients with the tricuspid aortic valve (TAV). 4D flow magnetic resonance imaging (MRI) was performed a day before aortic replacement surgery. Biomechanical and histological parameters, including assessing of wall strength, media degeneration, elastin, and cell content were analyzed from the resected AA samples. Results. WSSs were greater in the outer curves of the AA compared to the inner curves in all TAA patients. WSSs correlated with media degeneration of the aortic wall (ρ = -0.48, p <0.01), elastin content (ρ = 0.47, p <0.01), and aortic wall strength ( ρ = -0.49, p = 0.029). Subsequently, the media of the outer curves was thinner, more rigid, and tolerated lower failure strains. Failure values were shown to correlate with smooth muscle cell (SMC) density (ρ = -0.45, p <0.02), and indicated the more MYH10+ SMCs the lower the strength of the aortic wall structure. More macrophages were detected in patients with severe media degeneration and the areas with lower WSSs. Conclusions. The findings indicate that MRI-derived WSS predicts pathological and biomechanical changes in the aortic wall in patients with TAA and could be used for identification of high-risk patients.